Peran Lembaga Amil Zakat Infaq Shadaqah Muhammadiyah (Lazismu) Asahan dan Medan dalam Pengembangan Pendidikan Islam Bagi Siswa MTS dan MA - Erdianto, Rudi; Haidir, Haidir; Sinaga, Ali Imran (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
This study uses a qualitative approach to gain an in-depth understanding of the role of the Muhammadiyah Zakat, Infaq, and Shadaqah Institution (LAZISMU) in Asahan and Medan in supporting the development of Islamic education for students of Madrasah Tsanawiyah (MTs) and Madrasah Aliyah (MA). Data was collected through non-participatory observation, in-depth interviews with key informants (LAZISMU chairperson, school principals, teachers, and beneficiary students), and documentary studies of program reports and institutional archives. Data analysis employed the interactive model of Miles and Huberman, with validity testing through source triangulation, member checking techniques, and referential adequacy. The research findings indicate that LAZISMU's educational programs, such as the Mentari Scholarship, Sang Surya Scholarship, and School Kit, significantly contribute to improving access to and the sustainability of education for students from underprivileged families. These programs reduce the risk of school dropout and enhance students' motivation to learn and their engagement in school. LAZISMU's transformative approach through Islamic development activities, such as Qur'an memorization, Ramadan boarding schools, and spiritual training, further strengthens the formation of religious character and discipline among students. These findings indicate that professionally managed zakat not only functions as charitable assistance but also as an instrument for sustainable and value-based educational development. This study provides empirical contributions to the discourse on Islamic philanthropy by emphasizing the importance of value-based philanthropy in shaping intellectually and spiritually superior Muslim generations at the local level.